Protest Crowds through the Lens of Distributed Cognition. - Wagoner, Brady; Awad, Sarah H.; Power, Séamus A. (Social Research)
How are ideas transformed into collective causes that can rally and sustain protest crowds? We present a theoretical framework of crowd mobilization through the perspective of distributed cognition. We look at protest crowds as distributed processes that happen across brains, bodies, social interactions, and material-technological resources. This perspective is illustrated by protest crowd dynamics as they are facilitated by social interaction, symbols, narrative forms, and physical and virtual spaces.